2018
DOI: 10.1371/journal.pone.0205813
|View full text |Cite
|
Sign up to set email alerts
|

Paramedics’ perceptions of the care they provide to people who self-harm: A qualitative study using evolved grounded theory methodology

Abstract: BackgroundSelf-harm (SH) accounts for over 5% of the workload of emergency ambulance services, and therefore Paramedics are often the first health professional in contact with people who SH. The authors of this paper have reported elsewhere the significant gaps in our understandings which exist surrounding this early care interaction, and some of the challenges paramedics and opportunities in paramedic care for people who SH. This study aimed to explore paramedics’ perceptions of caring for those who SH using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…An interview guide was developed prior to conducting the interviews (S1 File). This guide was informed by the researcher's experience working as a paramedic as well as existing literature on emergency responder experiences [32,33]. One pilot interview was conducted by JWY with a part-time paramedic in order to assess whether questions were phrased clearly for the participant, and also to allow the researcher to become familiar with using the interview guide in practice [34,35].…”
Section: Interviews and Analysismentioning
confidence: 99%
“…An interview guide was developed prior to conducting the interviews (S1 File). This guide was informed by the researcher's experience working as a paramedic as well as existing literature on emergency responder experiences [32,33]. One pilot interview was conducted by JWY with a part-time paramedic in order to assess whether questions were phrased clearly for the participant, and also to allow the researcher to become familiar with using the interview guide in practice [34,35].…”
Section: Interviews and Analysismentioning
confidence: 99%
“…The third aspect of mental health literacy is a person's attitude towards mental illness and treatment (Jorm et al, 1997). McCann et al (2018a) suggest paramedics generally have positive attitudes towards mental illness and are supportive of treatment, yet frequently report frustration when attending to patients who call for mental illness (Rees et al, 2018). The conclusion drawn by McCann et al (2018a) is that paramedics have a positive attitude towards mental illness in general but have a negative view of patients who use emergency services for mental illness.…”
Section: Knowledge Of Mental Health Treatmentmentioning
confidence: 99%
“…More specifically, paramedics consider EMS to lack the appropriate resources to help patients with mental illness (McCann et al, 2018a) or that mental illness is not a life-threatening condition and, therefore, the use of emergency services in these situations is inappropriate (Ford-Jones and Chaufan, 2017;Prener and Lincoln, 2015). Two themes emerged across several studies in regard to the source of paramedics' frustration: one, that attending calls related to mental illness draws resources away from "more important" jobs (Rees et al, 2018;Hutchison et al, 2019) and two, that the EMS system was not appropriately resourced to help patients with mental illness without physical illness or injury (Cook, 2020;McCann et al, 2018a). Rees et al (2018) reported common problems for paramedics when attending calls related to mental illness include compassion fatigue as a result of attending the same type of job (e.g.…”
Section: Knowledge Of Mental Health Treatmentmentioning
confidence: 99%
See 2 more Smart Citations